Purification of DNA polymerase II stimulatory factor I, a yeast single-stranded DNA-binding protein. - Brown, W C (1990)
Incidental to the purification of yeast DNA polymerase II was the observation that various chromatographic fractions contained activities that stimulated synthesis by this polymerase. In this paper we report the purification and initial characterization of one such factor, stimulatory factor I (SFI). SFI, which is associated with an apparent complex of three polypeptides of 66, 37, and 13.5 kDa, binds preferentially to single-stranded DNA, possibly explaining its ability to stimulate DNA polymerase II. Single-stranded DNA-binding activity is associated with the 66-kDa polypeptide.